The Use of Javanese Phonology in The Mountainous Region of Batang Regency: A Socio-Dialectological Study - Sriatun, Sriatun; Winarti, Daru; Salahuddin, Salahuddin (Jayapangus Press, 2025)
This article discusses the phonological and lexical variations of the Javanese language in Batang Regency, focusing on the geographic dialect framework. Using a dialectological approach, particularly within the framework of geographic dialect theory, this article analyzes the phonological variations of Javanese, including local sound variations, consonants, vowel and consonant sound correspondences, and the patterns of syllables formed. The research data consists of oral Javanese speech used by native speakers and residents of Bawang Subdistrict in Batang Regency. Based on data analysis, phonological variations were identified, including sound changes and syllable patterns. Sound changes included free variations such as vowel sound changes in the first syllable, vowel sound changes in the second syllable, vowel sound changes in both the first and second syllables, consonant replacement in the first syllable, and consonant replacement in the second syllable. Additional sounds were observed, including prosthesis and paragogee. Sound reductions, including apheresis and syncope, as well as sound shifts, were also found. Seven syllable patterns were identified, including V, VK, KVK, KKV, KKVK, KKKV, and KKKVK. These phonological variation data are then presented on a language map. Geographic factors are identified as the causes of Javanese language variations in Batang Regency.